2007
DOI: 10.1063/1.2747664
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of nitrogen related traps in InGaAsN with solar cell properties

Abstract: The thermal annealing of nitrogen related traps in p-type InGaAsN and GaAsN is investigated by deep level transient spectroscopy (DLTS). Upon annealing, an apparent recovery of the photovoltaic properties correlates with changes in the DLTS data observed for InGaAsN and GaAsN diodes and solar cells, revealing that a nitrogen related E1 (EC−0.20eV) center has an important role in governing the solar cell performance. The large electron capture cross section (∼8.9×10−15cm2) of this center indicates that this def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 7 publications
0
26
0
Order By: Relevance
“…Dilute nitride based materials, such as InGaAsN and InGaNAsSb, have been studied for such an application [3,4]. However, it was found that nitrogen-related defects constrained the performance of these dilute nitride-based photovoltaic cells, which resulted in low open circuit voltage (V OC ) [5,6]. GaNAsSb was firstly proposed by Ungaro et al [7] as a potential GaAs-based small bandgap (o1.4 eV) material.…”
Section: Introductionmentioning
confidence: 98%
“…Dilute nitride based materials, such as InGaAsN and InGaNAsSb, have been studied for such an application [3,4]. However, it was found that nitrogen-related defects constrained the performance of these dilute nitride-based photovoltaic cells, which resulted in low open circuit voltage (V OC ) [5,6]. GaNAsSb was firstly proposed by Ungaro et al [7] as a potential GaAs-based small bandgap (o1.4 eV) material.…”
Section: Introductionmentioning
confidence: 98%
“…The presence of nitrogen as well as technological limitations of these materials involve generation of many structural defects, especially those associated with incorporation of N atoms into the crystal lattice, which can significantly affect deterioration of many electrical and optical properties of the material [6][7][8]. Electrically active deep-level defects in the band gap can influence the density of charge carriers, their diffusion lengths, mobility and lifetime or efficiency of luminescence, leading finally to device degradation.…”
Section: Introductionmentioning
confidence: 99%
“…These include the N-N dimer, N-As, and N-Sb interstitial pairs. 19,21,[39][40][41] If the defect was a N-N dimer, both its average distance to the closest In atom and mass would be far from the values we extracted from our fits. Therefore we can exclude this possibility.…”
Section: Discussionmentioning
confidence: 88%